Age-related cataract without surgery is related to exacerbated depression symptoms: a cross-sectional study of Chinese adults from Anhui, China - Wang, Tao; Li, Hexia; Cao, Quangang (Frontiers in Medicine, 2024)
Objective: The present study sought to evaluate the relationship between age-related cataracts, a prevalent ocular condition among the elderly, and the occurrence of depressive symptoms within a cohort of Chinese adults residing in Anhui, China. Methods: A survey involving 252 Chinese individuals aged 65 years and older was conducted at Lu'an People's Hospital. Depressive symptoms were assessed utilizing the Hamilton Depression Scale (HAMD) consisting of 17 items, while age-related cataracts were clinically classified according to the Lens Opacities Classification System (LOCS) III. Depressive symptoms were identified by a HAMD score exceeding 7. Logistic regression analyses were employed to determine the odds ratios (OR) and 95% confidence intervals (CI) pertaining to the association between age-related cataracts and depressive symptoms. Results: Among cataract patients aged 65 years and older, the prevalence of depressive symptoms was significantly higher compared to those under 65 years (mean scores of 8.17 ± 3.26 versus 5.18 ± 1.86, P < 0.001). Additionally, patients aged 65 years and above exhibited a diminished quality of life relative to patients aged under 65 years. The findings indicated that adults experiencing depressive symptoms reported lower monthly incomes (P = 0.036), lower educational attainment (P = 0.044), and living alone (P = 0.007). Furthermore, fewer elderly patients with depressive symptoms received surgical treatment (15 compared to 61, P = 0.011) in contrast to those who did not have depressive symptoms. Multivariate analysis revealed that the presence of depressive symptoms was significantly correlated with a lack of formal education (P = 0.048), reduced income (P = 0.003), solitary living arrangements (P = 0.025), and the presence of cataracts without surgical intervention (P = 0.007). Conclusions: These findings suggested a significant association between age-related cataracts and depressive symptoms among older adults. Specifically, cataracts that remain untreated surgically were notably linked to depression in elderly patients. It is recommended that initiatives and resources be directed towards surgical treatment programs for cataracts in individuals exhibiting depressive symptoms.